Poly(L-Lactide)/Poly(∊-Caprolactone) and Collagen/β-Tricalcium Phosphate Scaffolds for the Treatment of Critical-Sized Rat Alveolar Defects: A Microtomographic, Molecular-Biological, and Histological Study. (July 2016) - Ekin, Omer; Calis, Mert; Aliyev, Ali; Yar, Seda Atiye; Korkusuz, Petek; Bilgic, Elif; Aydin, Halil Murat; Celik, Hakan Hamdi; Ozgur, Figen; Vargel, Ibrahim
Objective: To determine the efficacy of a newly developed scaffold (col/β-TCP) in a preclinical rat model as compared with the gold standard treatment (autograft) and control scaffolds (PLLA/PCL). Design: Fifty-six Sprague-Dawley rats were randomized into four experimental groups, and critical-sized alveolar defects (7 × 4 × 3 mm) were created in each animal. Group A was the blank defect group, group B received autograft, group C received col/β-TCP scaffolds, and group D received PLLA/PCL blend scaffolds to fill the bone defects. New bone formation was assessed radiomorphometrically, histomorphometrically, and molecular-biologically at 1 and 4 months following surgery. Results: Radiomorphometrically, the best new bone volume rate at 1 month (43.7%) and 4 months (45.4%) was observed in the autograft group, and the difference was significantly higher than in the other three groups ( P ≤ .005, P ≤ .001, P ≤ .001 for 1 month and P = .004, P ≤ .001, P ≤ .001 for 4 months). Even though the new bone volume rate in the col/β-TCP group (21.5%) was higher than that of the PLLA/PCL group (18.2%), the difference was not significant ( P = .08). Molecular-genetic analysis revealed significantly higher BSP and ALP gene expression levels in the autograft and col/β-TCP groups than in the blank defect group ( P = .002 and P = .004). Conclusion: The engineered tissue scaffolds described herein have great potential as an alternative treatment option when cost, donor region morbidity, and duration of hospitalization are considered.